1971
DOI: 10.1073/pnas.68.1.177
|View full text |Cite
|
Sign up to set email alerts
|

A Rapidly Acting Metabolite of Vitamin D 3

Abstract: A vitamin D, metabolite in intestine more polar than 25-hydroxy-vitamin Vitamin D is believed to function in the regulation of calcium absorption from the gut by controlling the expression of genetic information (1, 2). Several groups hypothesize that vitamin D induces the synthesis of mRNA and a special protein(s) that comprises part or all of a calcium transport system in the intestinal mucosa cell. A calcium-binding protein induced by vitamin D has been isolated from the chick gut (3), and the vitamin has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
1

Year Published

1971
1971
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(22 citation statements)
references
References 19 publications
1
20
1
Order By: Relevance
“…than 25-(OH)D3 to initiate intestinal calcium transport (4)(5)(6). The kidney is the site of synthesis of 1,25-(OH)2D3 from 25-(OH)D3 (7); this observation was confirmed by Gray et al (8).…”
supporting
confidence: 73%
“…than 25-(OH)D3 to initiate intestinal calcium transport (4)(5)(6). The kidney is the site of synthesis of 1,25-(OH)2D3 from 25-(OH)D3 (7); this observation was confirmed by Gray et al (8).…”
supporting
confidence: 73%
“…They concluded that this material, which they called peak 5, was formed in the intestinal nuclei and other target cells from 25-hydroxycholecalciferol. This polar compound became of great interest when Kodicek et al (1970), Haussler et al (1971 and Myrtle & Norman (1971) showed that it was more active than D3 in producing increased intestinal absorption of calcium. A major advance occurred very shortly afterwards when Fraser & Kodicek (1970) established conclusively that the kidney was the unique site of biosynthesis of this biologically active vitamin D metabolite.…”
Section: Historical Aspects (I) Early Observations Of the Aetiology Omentioning
confidence: 99%
“…When given intravenously as a single-pulse dose, 1,25-(OH)2D3 has been shown to act more rapidly than 25-OHD3 in stimulating intestinal calcium transport (11,12) and in activating the bone calcium mobilization system (12,13). Although more active than 25-OHD3 in the intestinal calcium transport system (11-13), 1,25-(OH)2D3 was equally as active as 25-OHD3 in the bone calcium mobilization response and was much less active in the cure of rickets in rats (12).…”
Section: Introductionmentioning
confidence: 99%